Disability at the intersections. Issue 10 (12th September 2019) - Shifrer, Dara; Frederick, Angela
Abstract: Complete and accurate understandings of stratification depend on more regular consideration of disability. To build sociologists' recognition of disability as a socially constructed axis of stratification, we first demonstrate the construction of the disability category through classic legitimating processes: moral attributions, biological attributions, separation, and dichotomization. Expanding understandings of basic processes of stratification, we then document the centrality of disability in the social construction of class, race, gender, sexual orientation, and age. Finally, we show various ways disability functions as an axis of stratification in intersection with other key axes of stratification.